Effects of a synthetic analog of the bovine appeasing pheromone on the overall welfare of dairy calves from birth through weaning - J. Garcia-Alvarez; E. Teruel; A. Cozzi; E. Harris; S.M. Rutter; A. Beaver (Journal of Dairy Science)
ABSTRACT: Environmental enrichment in the form of synthetic analogs of appeasing pheromones have shown promising results in improving the welfare of domestic animals, including dogs, pigs, horses, and cattle. The main objective of this study was to determine if the use of the bovine appeasing pheromone (BAP) would improve the welfare of dairy calves; therefore, in this randomized controlled trial, 72 Holstein Friesian dairy calves were housed in individual hutches after birth and were randomly allocated to receive BAP or a placebo once every 2 wk from birth through weaning. After weaning, calves were moved to group hutches according to treatment for 4 additional weeks. It was hypothesized that dairy calves treated with BAP would display fewer signs of stress compared with calves receiving the placebo during the weaning process. To operationalize stress, calves were fitted with triaxial accelerometers on the hind leg after birth, and activity levels were monitored throughout the experiment. Data on live weight gain (ADG) and cortisol levels in saliva and hair were also obtained. Calves were fitted with heart rate monitors every week for at least 24 h to assess heart rate variability (HRV). The use of BAP had a positive effect on ADG after weaning and during group housing and resulted in increased resting time after weaning. Moreover, BAP was associated with a reduction in the activation of the neuroendocrine system evidenced by higher HRV parameters after weaning, including increased standard deviation of beat to beat of normal sinus beats and root mean squares of successive differences. These results suggest a potential welfare benefit of the use of BAP during the artificial rearing of dairy calves.